Caracterização físico-química do amido e da farinha da fruta-pão (Artocarpus altilis) e aplicação em pães de forma - Cavallini, Olívia Furlan (2015)
The breadfruit is a fruit rich in vitamins and minerals which can be extracted starch or processed to the form of flour increasing its shelf life. This flour can partially replace the wheat flour for producing bread products. The aim of this study was to extract and analyze some physical, chemical and technological characteristics of native starch breadfruit, and perform the physical-chemical characterization of this fruit flour and mixed flours and verify the viability of the preparation of bakery. The breadfruit starch was subjected to moisture, water binding capacity cold (WBCC), swelling power (SP), solubility index (SI), syneresis, scanning electron microscopy (SEM) and X-ray diffraction. The corn starch was analyzed for comparison. The breadfruit starch showed higher moisture (18.32%), WBCC (80.33%), SP (198.71 g/g to 90 0C), SI (7.22% at 90 0C) and syneresis (2. 69 ml) compared to the corn starch. By SEM analysis, it was found that breadfruit starch granules showed lower than maize starch, but both with a polyhedral shape. The X-ray diffraction allowed to classify corn starch as type A and the breadfruit as type B. Flour analyzed samples contained a percentage of breadfruit flour 0% (control), 5%, 10%, 15%, 20% and 100% and were subjected to moisture, ash, lipids, carbohydrates, protein, energy, total, soluble and insoluble fiber, pH, color and particle size. The same percentage of replacement were used in the preparation of bread, analyzed for moisture, weight, bulk and specific bulk, height, texture profile, sensory acceptance and purchase intent. The replacement of wheat flour by breadfruit flour influence the particle size mixtures, reduced the protein from 10.8% to 3.99%, increased the percentage of carbohydrates, ash and pH from 73.84%, 0.52%, 5.94 to 83, 10%, 2.19% , 6.34, respectively. However, for moisture, lipid content and overall difference in color of the samples showed no significant influence of the percentage of replacement. The flour breadfruit presented a greater percentage of total fiber (21.17%), soluble (10.39%) and insoluble (10.77%). For bakery increased substitution did not affect the moisture and weight of bread, except for the sample with 100% breadfruit flour which showed 41.28% moisture and weight of 588.65 g. For the remaining analyzes, the highest percentages of replacement negatively influenced the characteristics of the product. Regarding the physical and chemical characterization of the flour samples, increasing the replacement percentage influenced most of the evaluated parameters. For breads, formulations with high hedonic notes and better purchase intent were with replacement of 5% and 10%.